Performance of Kentucky bluegrass, tall fescue, and buffalograss under line source irrigation - Ervin, Erik H., author; Koski, Anthony James, 1957-, advisor; Hughes, Harrison, committee member; Smith, D. N., committee member (Colorado State University. Libraries, 1995)
Increasing demand for the scarce water resources of the semi-arid western United States, coupled with the highly visible practice of landscape irrigation, has fostered increased concern regarding turfgrass water conservation. Accordingly, the objectives of this research were to determine the relative performance of Kentucky bluegrass (Poa pratensis L.), turf-type tall fescue (Festuca arundinacea Schreb.), and buffalograss [Buchloe dactyloides (Nutt.) Engelm.] under increasing levels of water stress; to examine the effects of differential tillage depth of a previously compacted soil at sod establishment on rooting characteristics and subsequent drought resistance; and to compare this study's findings concerning the irrigation required to maintain acceptable turfgrass quality with irrigation requirements predicted by the weather station estimated evapotranspiration (ET)-models used by Denver and other Colorado communities. The effects of irrigation amount, turfgrass type, and tillage depth at sod establishment on rooting characteristics, water use, visual quality and leaf firing, and canopy temperatures were investigated at Fort Collins, CO, on a Nunn clay loam (Aridic Argiustoll, fine, montmorillonitic, mesic) soil. A line source irrigation system was used to apply five irrigation treatments based on percent replacement of reference ET. In 1993, irrigation treatments at the following levels were applied every three days: 80%, 70%, 60%, 45%, and 20% of reference ET. In 1994, the irrigation treatments were 95%, 85%, 75%, 60%, and 35% of reference ET. Five turfgrass types and two tillage depths at sod establishment were arranged in four randomized complete blocks. The five turfgrass types were: 'Nustar' Kentucky bluegrass, a turf type tall fescue/Kentucky bluegrass mix, a turf type tall fescue blend, '609' buffalograss, and 'Prairie' buffalograss. The two tillage depths were ~2.5 and ~15.0. In both 1993 and 1994 no effect of tillage treatment was measured for any of the parameters sampled. At the end of both years, the tall fescue blend had more total root density (down to 90 cm) than Kentucky bluegrass. Consequently, the tall fescue extracted greater amounts of soil moisture from deep in the soil (30-90 cm). These results were reflected in significantly higher quality ratings, lower leaf firing ratings, and lower canopy temperatures as irrigation level decreased for the tall fescue blend relative to the Kentucky bluegrass. Buffalograss quality was not significantly affected by any of the irrigation treatments in either year, a confirmation of its reported superior drought resistance. Results indicate that buffalograss avoids drought better than turf type tall fescue and that turf type tall fescue avoids drought better than Kentucky bluegrass. It is concluded that acceptable turfgrass quality can be maintained in Colorado by irrigating these three turfs every three days by adjusting alfalfa reference ET's with an irrigation coefficient of 0. 70 for Kentucky bluegrass, 0.60 for turf type tall fescue, and 0.30 for buffalograss.
Keywords: Turfgrasses; Sprinkler irrigation